(untitled) (Research, Society and Development, 2022)
The crescent number of students with intellectual deficiency registered in regular schools challenges education professionals regarding to adequacy of scholar’s curriculum and the school itself, in so that students have conditions to develop their intellectual and adaptational functions, according to their individual needs. This present research intended to accomplish one systematic revision of special education articles, focused on intellectual deficiency, interdisciplinarity and teacher training. The association of the two terms, interdisciplinarity and intellectual deficiency, are the guiding axis of this integrative systematic review. This study analyzed, at first moment, articles from 1980 to 2020, at Periodic Portal Virtual Library from CAPES using the following keywords: Intellectual Deficiency, Interdisciplinarity and TeacherTraining. A total of 275 articles were found according to inclusion and exclusion criterions, in which 16 articles were selected for full reading. The result leads to conclude that the interdisciplinary work, despite being recognized by several theorists as a methodological tool that could collaborate for one meaningful learning of special education students, still needs to be recognized as one learning facilitating element between educational professionals. The interdisciplinary work is not effective in practice, it is necessary that educators take ownership of this methodology, mostly in special education.